Selective Attention and Sensory Modality in Aging: Curses and Blessings - Van Gerven, Pascal W. M.; Guerreiro, Maria J. S. (Frontiers in Human Neuroscience, 2016)
The notion that selective attention is compromised in older adults as a result of impaired inhibitory control is well established. Yet it is primarily based on empirical findings covering the visual modality. Auditory and especially, cross-modal selective attention are remarkably underexposed in the literature on aging. In the past 5 years, we have attempted to fill these voids by investigating performance of younger and older adults on equivalent tasks covering all four combinations of visual or auditory target, and visual or auditory distractor information. In doing so, we have demonstrated that older adults are especially impaired in auditory selective attention with visual distraction. This pattern of results was not mirrored by the results from our psychophysiological studies, however, in which both enhancement of target processing and suppression of distractor processing appeared to be age equivalent. We currently conclude that: (1) age-related differences of selective attention are modality dependent; (2) age-related differences of selective attention are limited; and (3) it remains an open question whether modality-specific age differences in selective attention are due to impaired distractor inhibition, impaired target enhancement, or both. These conclusions put the longstanding inhibitory deficit hypothesis of aging in a new perspective.